Contribution Under the Federal Securities Laws (Washington University Law Quarterly, 1975)
It is not uncommon today for a single securities case to include several cross-claims or third-party claims for contribution. Yet the paucity of precedent in this area of federal securities law has given the courts little guidance for dealing with such claims. Courts cannot analogize to legal analysis of contribution claims in other federal actions; except for admiralty, no such body of law exists. Nor is there a unified state approach to which the courts can turn. The absence of precedents, however, leaves federal courts relatively free to choose contribution rules adapted to the securities setting. To explore some of these rules and the problems they raise in the special field of securities law, this Article will examine the history of contribution under federal securities law, the relationship between contribution and indemnity, and the procedural problems encountered in computing and allocating contribution shares.
Keywords: Contribution (Law); Commercial law